Evaluation of the Merdeka Curriculum Program at SMKN 1 Luak - Liesye Afriyanti; Fahmi Rizal; Muhammad Giatman; Waskito (Jurnal Penelitian Pendidikan IPA, 2025)
Education plays an important role in improving human resources and shaping adaptive character. To address post-pandemic learning challenges, Indonesia introduced the Merdeka Curriculum, emphasizing flexibility and competency development. This study evaluates the Merdeka Curriculum implementation at SMKN 1 Luak, Lima Puluh Kota Regency, West Sumatra, using the CIPP (Contextual, Input, Process, Product) model. The evaluation covers the 2023/2024 academic year, following its introduction in 2022. A mixed-method approach (qualitative and quantitative) was used for data collection through observations, interviews with teachers, students, and administrators, and analysis of relevant curriculum documents. The results indicate that the context aspect (National Education Standards and School-Level Curriculum) is very good (91.11%). The input aspect (teacher qualifications, infrastructure, reference books) is generally good, but there are shortcomings in qualified teachers, reference books, and subject guidelines. The learning process is rated as adequate (77.18%), with challenges in teaching strategies and student engagement. Student learning outcomes were rated as adequate (79.12%), with room for improvement in critical thinking and problem-solving skills. The Merdeka Curriculum positively impacts education quality, but improvements in facilities, teacher training, and motivation are needed to optimize its effectiveness. These findings suggest schools with similar contexts can benefit by focusing on teaching infrastructure and professional development.